History, Progress, and Prospects of Urban Fringe Research in China: An Idiosyncratic Synthesis from a Spatial Perspective - Zhi Li; Lixin Zhang; Tian Hu; Yifei Wu (Land)
Urban fringes, as transitional zones between urban and rural systems, have played a pivotal role in China’s rapid urban expansion. Though there have been very rich urban fringe studies in China, little efforts have been made to introduce this research progress to global peers. To fill this gap, this paper presents an idiosyncratic synthesis based on the relevant Chinese literature, from a spatial perspective—with urban fringes as a land system type of its own kind. We first recap the historical trajectory of urban fringe research in China, revealing its progression from early international influences to context-specific investigations shaped by China’s unique governance and socio-economic conditions. We then introduce, in more detail, the main research progresses on revealing the spatial patterns, underlying mechanisms, and governance practices of China’s urban fringe areas. We argue for studying urban fringes as part of and the critical zone for coupling urban–rural systems, and call for a holistic, inclusive approach in future studies. Specifically, we identify three research prospects: (1) understanding the new patterns of social-environmental dynamics in China’s New Era; (2) promoting spatial governance from a coupled urban–rural system perspective; and (3) leveraging artificial intelligence for producing spatially actionable knowledge.